Scooby-Doo! World of Mystery 28 South Africa - Diamond Mines - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
The gang find a diamond with a curse on it and get to the bottom of a mystery down a mine shaft!
Keywords: Juvenile literature-Fiction